Antarctica on the edge - Veitch, Andrew; Films for the Humanities and Sciences (Princeton, NJ : Films for the Humanities & Sciences, 1997)
Explores the ecology of Antarctica. With temperatures rising, delicate ecosystems are on the verge of collapse. Experts predict that this crisis in Antarctica could portend flood disaster for many coastal cities around the globe
Title from title screen
Photography, Phil Bye ; graphics, Peter Everest ; editor, Ryshard Opyrchal ; executive producers, Grant McKee, Sue Inglish
Keywords: Ecology -- Antarctica; Antarctica